2019
DOI: 10.1002/mrd.23241
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibitor protects chemerin‐induced human granulosa‐lutein cells from apoptosis by inhibiting the p53/p21waf pathway

Abstract: Dysregulation of the cell cycle is common in human tumorigenesis. Therefore, CDK4/6 inhibitors targeting the cell cycle have been developed, and their antiapoptotic effects have been highly correlated with potential clinical therapies. The aim of this study was to identify the regulatory effect of the CDK4/6 inhibitor palbociclib on chemerin‐induced apoptosis of immortalized human granulosa‐lutein (hGL) cells and to elucidate its fundamental mechanism of action. Palbociclib enhanced antioxidative enzyme genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…This effect was not observed in the presence of p21 co-expression, suggesting that palbociclib and p21 competed for the stabilization of cyclin D3-CDK4 complexes. Furthermore, recent studies [44,45] showed a potential "protective" role of palbociclib in granulosa cells in regard to chemerin, which is an adipokine secreted mainly from adipose tissue that causes reactive oxygen species (ROS) accumulation and triggers apoptosis in mouse granulosa cells. Evidence suggests that palbociclib has an antiapoptotic effect on immortalized human granulosa-lutein (hGL) cells treated with chemerin.…”
Section: Role Of Exogenous Cdk Inhibitors (Cdki) In the Ovarymentioning
confidence: 99%
“…This effect was not observed in the presence of p21 co-expression, suggesting that palbociclib and p21 competed for the stabilization of cyclin D3-CDK4 complexes. Furthermore, recent studies [44,45] showed a potential "protective" role of palbociclib in granulosa cells in regard to chemerin, which is an adipokine secreted mainly from adipose tissue that causes reactive oxygen species (ROS) accumulation and triggers apoptosis in mouse granulosa cells. Evidence suggests that palbociclib has an antiapoptotic effect on immortalized human granulosa-lutein (hGL) cells treated with chemerin.…”
Section: Role Of Exogenous Cdk Inhibitors (Cdki) In the Ovarymentioning
confidence: 99%
“…One targeted therapy for CDK inhibition is palbociclib, which may slow the growth of advanced stage breast cancers. In line with this, Palbociclib was used to protect chemin-induced human granulosa cells from apoptosis, acting to inhibit the p53/p21 pathway (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 95%